Academic Anxiety and Online Gaming Addiction: The Moderation Effect of Emotional Regulation in Adolescent - Rinaldi, Martaria Rizky; Andartono, Sekararrum Wiwied; Anggawijayanto, Erydani (Universitas Negeri Surabaya, 2024)
Background: The rising prevalence of online gaming addiction among adolescents underscores the urgency of understanding the contributing factors. Psychological elements like academic anxiety and emotional regulation play significant roles in this context. Objective: This study aims to investigate the moderating effect of emotional regulation on the relationship between academic anxiety and online gaming addiction among adolescents. Method: A cross-sectional study design was employed, involving a sample of adolescents aged 17-21 years. Participants completed self-report measures assessing academic anxiety, emotional regulation, and online gaming addiction. Moderation analysis techniques were employed to analyze the data. Results: The findings revealed a significant positive correlation between academic anxiety and online gaming addiction, as well as a positive association between emotional regulation and online gaming addiction. However, the interaction between academic anxiety and emotional regulation was not statistically significant. Conclusion: The results underscore the importance of addressing academic anxiety and enhancing emotional regulation skills in preventing and managing online gaming addiction among adolescents. These findings have implications for both research and intervention efforts aimed at promoting healthier gaming habits and overall well-being in this population.